Agama Sebagai Pilar Moral Pada Tantangan Sosial Kontemporer Umat Islam Di Indonesia - Bina Prima Panggayuh; Muhammad Ridwan; Chika Novianti Putri Lestari; Kairu Alfa; Zahra Hanan Maulid (Yayasan Al-Afif, 2025)
This research examines the significance of religion as a moral foundation in addressing social challenges faced by Muslims in contemporary Indonesia. The study aims to explore how Islamic principles influence ethical conduct, foster social responsibility, and strengthen community engagement amid rapid modernization, technological development, and cultural globalization. Data were obtained through qualitative methods, including literature analysis, semi-structured interviews, and direct observation of community activities. The results indicate that adherence to Islamic teachings plays a crucial role in guiding moral choices, enhancing social solidarity, and offering practical solutions to ethical dilemmas in daily life. The research further emphasizes the importance of religious education, moral awareness, and active participation in community initiatives to reinforce ethical resilience. In conclusion, Islam functions not only as a source of spiritual guidance but also as a practical framework for moral orientation, providing both ethical guidance and social stability for Indonesian Muslims navigating complex contemporary societal issues.